Pengaruh Kepribadian dan Efikasi Diri Terhadap Pengambilan Keputusan Kepala SMA Negeri Di DKI Jakarta - Anugrah Meti Suryani; Mukhneri -; Matin - (Peneliti.net, 2018)
This study aimed to determine the effect of (1) personality, (2) self-efficacy, (3) decision making of thead master who are working at Senior High School in Jakarta District. Survey method with a quantitative-causal approach using path analyses was used to in this research. This survey was conducted from February to May, 2018 involving 89 head master in a District as samples. This sampling was determined randomly by Slovin formula. The findings of this study indicated: first, there is a positive direct effect of personality on decision making. Second, there is a positive direct effect of self-efficacy on decision making. Third, there is a positive direct effect of personality on self-efficacy. Based on the findings, it is suggested for the Principal which is the position is as a manager in the school to be a good role model for the teachers in respecting and appreciating others.